2023
DOI: 10.1002/adfm.202213941
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Transport Enhancement Mechanism in Highly Efficient Antimony Selenide Thin‐Film Solar Cell

Abstract: Exhibiting outstanding optoelectronic properties, antimony selenide (Sb 2 Se 3 ) has attracted considerable interest and has been developed as a light absorber layer for thin-film solar cells over the decade. However, current state-of-theart Sb 2 Se 3 devices suffer from unsatisfactory "cliff-like" band alignment and severe interface recombination loss, which deteriorates device performance. In this study, the heterojunction interface of an Sb 2 Se 3 solar cell is improved by introducing effective aluminum (Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…When the bias voltage exceeds the kink point, which corresponds to the trap-filled limit voltage, the injected carrier fills the trap states in the TFL region ( V TFL ). [ 28 ] Then the defect density of the Sb 2 Se 3 thin film can be determined using the V TFL value according to the following equation [ 5 ]: where L represents the thickness of the Sb 2 Se 3 thin film, q represents the elementary charge, ε r represents the permittivity of the Sb 2 Se 3 and ε 0 represents the vacuum permittivity. The defect densities were calculated to 2.06 × 10 14 cm −3 and 1.86 × 10 14 cm −3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the bias voltage exceeds the kink point, which corresponds to the trap-filled limit voltage, the injected carrier fills the trap states in the TFL region ( V TFL ). [ 28 ] Then the defect density of the Sb 2 Se 3 thin film can be determined using the V TFL value according to the following equation [ 5 ]: where L represents the thickness of the Sb 2 Se 3 thin film, q represents the elementary charge, ε r represents the permittivity of the Sb 2 Se 3 and ε 0 represents the vacuum permittivity. The defect densities were calculated to 2.06 × 10 14 cm −3 and 1.86 × 10 14 cm −3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…When the bias voltage exceeds the kink point, which corresponds to the trap-filled limit voltage, the injected carrier fills the trap states in the TFL region (V TFL ). [28] Then the defect density of the Sb 2 Se 3 thin film can be determined using the V TFL value according to the following equation [5]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have shown that the average carrier lifetime of the CdSe thin film is less than 200 ps, which is the most important factor greatly limiting the efficiency. As the DFT calculation mentioned above, the Te element serves as a good passivation for the CdSe thin films that can reduce the hole capture coefficient and the recombination rate, hence it is theoretically possible to increase the carrier lifetime . Time-resolved photoluminescence (TRPL) mapping was used to study the photogenerated carrier dynamics in thin films.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1–5 ] In addition to this material's favorable combination of properties; boasting a nearly ideal 1.18 eV band gap, [ 6 ] high absorption coefficient, [ 7–9 ] low toxicity and high stability, [ 10–12 ] Sb 2 Se 3 has further demonstrated a high degree of versatility. It is capable of being deposited in both substrate [ 13–17 ] and superstrate [ 18–26 ] geometries and with a wide variety of deposition techniques; from low temperature solution‐based methods, [ 21,24–26 ] to high temperature physical vapor deposition approaches. [ 13–15,18–20,22,23 ] This has led to a rapid improvement in performance with a record power conversion efficiency ( PCE ) of 10.6% for the pure selenide composite [ 25 ] and 10.7% for the Sb 2 (S,Se) 3 alloy.…”
Section: Introductionmentioning
confidence: 99%